Management Accounting System Dimensions as Mediating The Effect of Decentralization and Environmental Uncertainty on Managerial Performance - Glen Lazwardi Qurba (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
This research aims to determine and examine the effect of Decentralization and Environmental Uncertainty on Managerial Performance with the Management Accounting System as Intervening Variables in STARKES Accredited Hospitals in Bandung. The research method used is a combination method: sequential explanatory design. This study uses primary data consisting of questionnaires and interviews. The total population of this study is 11 hospitals. This research is hypothesis testing research. The research model was analyzed using PLS (Partial Least Square) analysis. The analysis results show that the management accounting system can mediate the effect of decentralization on managerial performance, where the company is more decentralized and supported by a high management accounting system, which will produce an adequate managerial performance. In addition, the management accounting system can mediate the effect of environmental Uncertainty on managerial performance. The higher the environmental Uncertainty and supported by the high use of MAS (Management Accounting System), the more adequate managerial performance.